Kontribusi Kepemimpinan Kepala Sekolah dan Kinerja Guru terhadap Prestasi Siswa MTSN Kuranji Padang - Azvi Rahmi (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
Based on field observations, it is observed that student achievement in MTsN Kuranji Padang is still low. Researchers suspect that principal leadership and teacher performance affect student achievement in MTsN Kuranji Padang, therefore a research is conducted to test the truth. This study aims to reveal the contribution of principal leadership and teacher performance to student achievement discipline in MTsN Kuranji Padang. The hypothesis proposed in this research are: 1) principal leadership contributes to student achievement; 2) teachers' performance contributes to student preservation; 3) the principal's leadership and teacher performance contribute jointly to student achievement The population in this research is all students of MTsN Kuranji Padang. Sampling was done using Stratified Proportional Random Sampling technique. Selected samples were 76 people. Data were collected by questionnaire with Likert scale that has been tested for validity and reliability. Data were analyzed by correlation and regression technique. The results of the data analysis show that: 1) the principal's leadership contributes to student achievement of 14. 4%; 2) teacher performance contributes to student achievement of 14.2% and 3) principal's leadership and teacher performance together contributes to student achievement 19 4%. Based on descriptive analysis revealed that principal leadership, teacher performance and student achievement are both in fairly good category of ideal score